1995
DOI: 10.1002/ardp.19953280906
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationship Studies of CNS Agents, Part 25: 4,6‐Di(heteroaryl)‐2‐(N‐methylpiperazino)pyrimidines as New, Potent 5‐HT2A Receptor Ligands: A Verification of the Topographic Model

Abstract: A series of new 4,6-di(heteroaryl)pyrimidines containing an N-methylpiperazino group (6-13) or an ethylenediamine chain (15-20) in position 2 were synthesized and their 5-HT1A and 5-HT2A receptor affinities were determined. It was shown that the substituent effects on the 5-HT2A affinity are additive and could be described quantitatively. In a behavioral model it was also demonstrated that 6-11 are 5-HT2A receptor antagonists. The molecular modelling results suggested that the distances between the basic nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…The distances between groups crucial for activity, i.e. two aromatic centers and a basic nitrogen atom (or, following Andersen, the point (87), pizotifen) and then distance ranges between respective points were defined [60]. It was shown that the distances suggested previously by Andersen fit well into the determined ranges: In relation to both the above models, Westkaemper et al discussed geometric characteristics of 9-(aminomethyl)-9,10-dihydroanthracene (AMDA, 79) and its analogues (e.g.…”
Section: Chart 12mentioning
confidence: 99%
“…The distances between groups crucial for activity, i.e. two aromatic centers and a basic nitrogen atom (or, following Andersen, the point (87), pizotifen) and then distance ranges between respective points were defined [60]. It was shown that the distances suggested previously by Andersen fit well into the determined ranges: In relation to both the above models, Westkaemper et al discussed geometric characteristics of 9-(aminomethyl)-9,10-dihydroanthracene (AMDA, 79) and its analogues (e.g.…”
Section: Chart 12mentioning
confidence: 99%
“…The activity of 6-phenyl substituted compound 9 remained the same whereas the other compounds (13-15) were even less active. In our earlier papers dealing with pyrimidinepiperazines [10,11], 4,6-diaryl-substituted derivatives were always more active than monosubstituted ones. Thus it may be concluded that the methyl group in position 6 of a pyridine ring also brings about some interactions favorable for ligand-receptor complex formation.…”
Section: Resultsmentioning
confidence: 98%
“…As has been mentioned in the introduction, the majority of model compounds used for generating a 5-HT 2A antagonist pharmacophore contain a pyrimidine ring as the central core [10,11]. N-Methylpiperazine moiety in position 2 of pyrimidine supplies a basic nitrogen atom necessary for a proper ionic interaction with the respective aspartic acid (ASP155) of the 5-HT 2A receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…nists (54), and 2-or 4-(4-methylpiperazino) pyrimidines were described as 5-HT2A receptor antagonists (55). The pyrrolo- [2,3] pyrimidines are effective inhibitors of the protein-tyrosine kinase JAK3 (56).…”
Section: Discussionmentioning
confidence: 99%